2004
DOI: 10.1098/rsif.2004.0005
|View full text |Cite
|
Sign up to set email alerts
|

Design of biomimetic fibrillar interfaces: 2. Mechanics of enhanced adhesion

Abstract: This study addresses the strength and toughness of generic fibrillar structures. We show that the stress σ c required to pull a fibril out of adhesive contact with a substrate has the form σ c = σ 0 Φ(χ). In this equation, σ 0 is the interfacial strength, Φ(χ) is a dimensionless function satisfying 0 Φ(χ) 1 and χ is a dimensionless parameter that depends on the interfacial properties, as well as the fibril stiffness and radius. Pull-off is flaw sensitive for χ 1, but is flaw insensitive for χ < 1. The importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
279
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(289 citation statements)
references
References 17 publications
10
279
0
Order By: Relevance
“…In recent years, it is also becoming a valuable platform to study biological adhesion systems such as cell-cell contact (Chu et al, 2005;Chen and Gao, 2006b), cells on stretched substrates (Chen and Gao, 2006a), as well as adhesion systems of gecko and insects (Autumn and Peattie, 2002;Artz et al, 2003;Glassmaker et al, 2004;Hui et al, 2004;Gao et al, 2005;Spolenak et al, 2005;Yao, 2006;Yao andGao, 2006, 2007;Chen and Gao, 2007a;Chen and Soh, 2008). Among these studies, Yao (2006) and considered an interfacial crack model and showed that graded elastic materials can promote robust adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it is also becoming a valuable platform to study biological adhesion systems such as cell-cell contact (Chu et al, 2005;Chen and Gao, 2006b), cells on stretched substrates (Chen and Gao, 2006a), as well as adhesion systems of gecko and insects (Autumn and Peattie, 2002;Artz et al, 2003;Glassmaker et al, 2004;Hui et al, 2004;Gao et al, 2005;Spolenak et al, 2005;Yao, 2006;Yao andGao, 2006, 2007;Chen and Gao, 2007a;Chen and Soh, 2008). Among these studies, Yao (2006) and considered an interfacial crack model and showed that graded elastic materials can promote robust adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Recent interest in bio-inspired adhesives has motivated many researchers to fabricate microfibril arrays (Liu & Bhushan 2003;Peressadko & Gorb 2004;Chung & Chaudhury 2005;Crosby et al 2005;Glassmaker et al 2005Glassmaker et al , 2007Huber et al 2005;Northen & Turner 2005;Yurdumakan et al 2005;Kim & Sitti 2006;Majidi et al 2006;Aksak et al 2007;Gorb et al 2007;Greiner et al 2007; and to study their contact mechanics and adhesion (Jagota & Bennison 2002;Gao et al 2003Gao et al , 2005Persson & Gorb 2003;Hui et al 2004;Persson et al 2005;Spolenak et al 2005a,b;Tang et al 2005;Bhushan et al 2006;Tian et al 2006;Yao & Gao 2006;Chen & Gao 2007). Most of these studies focus on how the interface between the microfibrils and a smooth, hard substrate separates under a normal load.…”
Section: Introductionmentioning
confidence: 99%
“…Are there any restrictions on the geometrical parameters to attain flaw insensitivity and satisfy ELS in fibrillar structures? The concept of flaw insensitivity has been adopted to understand the mechanics of biological systems (Gao et al 2003;Persson 2003;Gao & Yao 2004;Glassmaker et al 2004;Hui et al 2004;Gao & Chen 2005;Gao 2006). In the state of flaw insensitivity, pre-existing crack-like flaw does not propagate or participate in the failure process so that the biological material failure occurs by uniform rupture at the limiting strength of the material.…”
Section: P Z Nf;mentioning
confidence: 99%
“…Various mechanical models have been developed to model specific hairy attachment systems (e.g. Hui et al 2002;Persson 2003;Glassmaker et al 2004;Hui et al 2004) within the framework of adhesive contact mechanics (e.g. Johnson et al 1971;Derjaguin et al 1975;Roberts & Thomas 1975;Muller et al 1980;Greenwood & Johnson 1981;Barquins 1988;Maugis 1992;Carpick et al 1996;Chaudhury et al 1996;Baney & Hui 1997;Johnson & Greenwood 1997;Barthel 1998;Greenwood & Johnson 1998;Kim et al 1998;Robbe-Valloire & Barquins 1998;Morrow et al 2003;Schwarz 2003;Chen & Wang 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation